2018
DOI: 10.1002/mc.22797
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ‐induced epithelial‐to‐mesenchymal transition in prostate cancer cells is mediated via TRPM7 expression

Abstract: Growth factors, such as the transforming growth factor beta (TGFβ), play an important role in promoting metastasis of prostate cancer, thus understanding how TGFβ could induce prostate cancer cell migration may enable us to develop targeted strategies for treatment of advanced metastatic prostate cancer. To more clearly define the mechanism(s) involved in prostate cancer cell migration, we undertook a series of studies utilizing non‐malignant prostate epithelial cells RWPE1 and prostate cancer DU145 and PC3 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 62 publications
3
45
0
Order By: Relevance
“…TRPM7 knockdown can disorganize cytoskeleton in mesenchymal MDA-MB-231 which lose their spindle-shaped morphology (Middelbeek et al 2012). TRPM7 is also known to participate in the epithelial-to-mesenchymal transition (EMT) in breast cancer (Davis et al 2014;Kuipers et al 2018;Sun et al 2018). In the present study, we also demonstrate that Cd 2+ exposure increases EMT markers N-Cadherin and Vimentin, while E-Cadherin is decreased in mammary epithelial cells.…”
Section: Discussionsupporting
confidence: 70%
“…TRPM7 knockdown can disorganize cytoskeleton in mesenchymal MDA-MB-231 which lose their spindle-shaped morphology (Middelbeek et al 2012). TRPM7 is also known to participate in the epithelial-to-mesenchymal transition (EMT) in breast cancer (Davis et al 2014;Kuipers et al 2018;Sun et al 2018). In the present study, we also demonstrate that Cd 2+ exposure increases EMT markers N-Cadherin and Vimentin, while E-Cadherin is decreased in mammary epithelial cells.…”
Section: Discussionsupporting
confidence: 70%
“…Here, our study also verified hypoxia insult caused a decrease of E-Cad protein expression, whereas an increase of N-Cad and vimentin protein expression. Reduction of HIF-1α, as well as downregulation of TRPM7, inhibited EMT and invasion of prostate cancer cells [15,16,42]. Our study is consistent with these findings, also showed that knockdown of both TRPM7 and HIF-1α inhibited EMT changes of androgen-independent prostate cancer cells induced by hypoxia, suggesting that TRPM7 regulates HIF-1α-mediated signaling to affect hypoxia-induced EMT in androgen-independent prostate cancer cells.…”
supporting
confidence: 91%
“…Downregulation of TRPM7 inhibited migration and invasion of prostate cancer cells with a mechanism involved in the regulation of epithelialmesenchymal transition (EMT) [15]. Besides, TRPM7 also mediated transforming growth factor beta-(TGF β-) induced EMT in prostate cancer [16]. TRPM7 overexpression was induced by hypoxia-ischemia in the rodent brain and mediated the corresponding brain injury, serving as a potential drug target for stroke [17].…”
Section: Introductionmentioning
confidence: 99%
“…These inhibitory NF-κβ effects could not be reversed by the incubation of cells with TGF-β, suggesting that these factors may synergistically induce invasion and EMT in prostate cancer cells [253]. TGF-β-mediated EMT can also be inhibited by Elf5 (through suppression of SMAD3 phosphorylation [254] or FoxA1 [255], and induced by SOX5 [105], CML, CRM1 [256], TRPM7 [257], or SENP1. Interestingly, the latter effect involves SENP1-induced deSUMOylation of SMAD4, leading to its inhibition and induction of EMT [258].…”
Section: Prostate Cancermentioning
confidence: 99%